Würde, Freiheit, Leiblichkeit: ethische Kategorien bei der Anwendung freiheitsentziehender Maßnahmen bei Menschen mit Demenz im Akutkrankenhaus - Ritzi, Sebastian; Kruse, Andreas (Zeitschrift für Gerontologie und Geriatrie, 2019)
The use of freedom-depriving measures (physical and medicinal restraints) in people with cognitive impairment or dementia in clinical care settings is of ongoing importance. At the same time, these coercive measures are not only heavily debated but also in most cases ethically questionable from the perspective of the ethics of human dignity. Usually, the ethical evaluation of freedom-depriving measures follows classical paradigms of medical ethics, such as the Principles of Biomedical Ethics by Beauchamp and Childress. To enrich the debate at this point, the ethical category of embodiment (“Leiblichkeit” ) is introduced and discussed after a short summary of the ethical problem at hand. The phenomenon of the living body that has received increasingly more attention in several sciences since the proclaimed “corporeal turn” enables new perspectives towards human dignity, freedom and deprivation of freedom: freedom-depriving measures do not take place in an invisible realm of ideas but are directly applied to the psychophysical unity that is the living body of a person. Thus, freedom-depriving measures are an intervention into the bodily autonomy of the human being and the personal freedom that is manifested in the living body. The concept of the living body (“Leib”) that is applied here, signifies more than just a physical object and is especially apt to capture the (inter)subjective dimension that has to be taken into account here. Finally, it will have to be investigated whether the use of medicinal restraints represents an especially serious interference into the sphere of human embodiment. Once introduced into the debate on freedom-depriving measures in clinical care, the category of embodiment can warrant decisive new emphases.